Lifestyle, product diversity, and product quality on repurchase intention: Empirical research on western skincare - Angga Oktavianto; Nur Afifah; Bintoro Bagus Purmono; Heriyadi Heriyadi; Ana Fitriana (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The objective of this research is to examine how lifestyle, product diversity, and product quality influence repurchase intention, as well as to investigate whether customer satisfaction can serve as a mediator.Method — The data collection method utilized an online questionnaire with a total of 224 respondents, aged at least 16 years old, who are users of the Shopee application and consumers of the Western skincare brand (Cerave), and have made purchases of the Western skincare brand (Cerave) on Shopee. Respondents were selected using a purposeful sampling method. Structural Equational Modeling (SEM) with the AMOS 24 tool was employed for data analysis.Result — The findings of this research indicate that lifestyle, product diversity, and product excellence have a positive and significant impact on repurchase intention. Customer satisfaction also demonstrates a positive and significant effect on repurchase intention, effectively mediating the relationships between lifestyle, product diversity, and product quality on repurchase intention.Novelty — This study focuses on a Western skincare brand as the subject of research, as such brands have received limited attention in prior research. This distinction sets our research apart from previous studies in the field.